Managing community through digital talk: Podcasting in the South Asian diaspora - Wolock, Lia (AoIR Selected Papers of Internet Research, 2013)
Podcasts have been variously labeled internet radio shows, talking blogs, and seen as examples of a completely new medium unto itself. Utilizing insights from the literature on the “broadcast talk” of radio and television, this paper argues for a careful consideration of the technologies and real uses of podcasting that create an experience that is more personal and temporally portable than radio, and yet more immediate, interactive, and “live” as compared to blogging. To understand podcasting, one should not think of it as a new medium, but rather must study the intricate ways “old media” and technologies—each with its own communicative characteristics—are an interwoven, thriving part of the digital landscape. Based on an overview of the English-language South Asian diasporic podcast-verse, and an analysis (making particular use of conversation analysis tools) of the South Asian Journalist Association’s web/podcast created using the phone-based BlogTalkRadio platform, this paper will first sketch the contours of an online community and address the manner in which the way it serves itself is shaped by technological affordances, community needs, and socio-cultural discourses about the South Asian diaspora. It will then, using the SAJA case study, consider the specific talk strategies of one web/podcast to understand how the use of this new configuration of technologies and discourses allows for a viable, variously bounded special interest community to be repeatedly talked into being.